PP.18.24: LONG-TERM INTIMA-MEDIA THICKNESS DEVELOPMENT IN HYPERTENSIVE SUBJECTS WITH WELL-CONTROLLED BLOOD PRESSURE LEVELS. (June 2015) - Puato, M.; Rattazzi, M.; Boschetti, G.; Zanon, M.; Buso, G.; Benetti, E.; Fania, C.; Pesavento, R.; Palatini, P.; Pauletto, P.
Abstract : Objective: The aim of this study was to evaluate in a long follow-up the time-course of carotid artery remodeling in a cohort of young grade I / II hypertensives hypertensive subjects. Design and methods: We studied 20 subjects with grade I / grade II hypertensives by assessing the B-mode ultrasound of mean carotid intima-media thickness (mean-IMT) and maximum IMT (M-MAX) in each carotid artery segment (common, bulb, internal), bilaterally. We therefore compared the ultrasound measurements of IMT with those recorded 5 and 10 years before. Office BP was taken three times by the same doctor at the time of the study. While the first 5-year follow-up was observational, in the second 5-year follow-up, lifestyle modifications and/or pharmacological therapy were started to control blood pressure (BP) levels. Results: BP levels were: -10 years 144 91 mmHg, - 5 years 143 93 mmHg, and 128 78 mmHg at the time of the study. In the first 5-year follow-up (-10 to -5 years), both mean-IMT and M-MAX increased significantly (p < 0.0005). In the subsequent 5-year follow-up (-5 years to baseline) which was also characterized by well controlled BP, mean-IMT slightly but significantly increased (p = 0.019), whereas M-MAX remained stable (NS, p = 0.908) (figure). Conclusions: In hypertensives when lifestyle interventions and/or pharmacological therapy are introduced to obtain well controlled BP levels, the pro-atherogenic remodelling, as expressed by the M-Max, improve. Conversely, the continued impact of a more, although albeit elevated BP burden might be responsible for the progression in mean-IMT which is likely to reflect some hypertrophy of the arterial media layer. The "pseudo-normalization" of the BP levels are not sufficient to eliminate the hypertensive status that continues to contribute to the atherosclerotic burden.